Denervation as a Treatment for Arthritis of the Hands: A Systematic Review of the Current Literature. (March 2023) - Zhu, Sarah L.; Chin, Brian; Sarraj, Mohamed; Wang, Eugene; Dunn, Emily E.; McRae, Matthew C.
Joint denervation has been proposed as a less invasive option for surgical management of hand arthritis that preserves joint anatomy while treating pain and decreasing postoperative recovery times. The purpose of this systematic review was to investigate the efficacy and safety of surgical joint denervation for osteoarthritis in the joints of the hand. EMBASE, MEDLINE, and PubMed databases were searched from January 2000 to March 2019. Studies of adult patients with rheumatoid arthritis or osteoarthritis of the hand who underwent joint denervation surgery were included. Two reviewers performed the screening process, data abstraction, and risk of bias assessment (Methodological Index for Non-Randomized Studies). This review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was registered with PROSPERO (#125811). Ten studies were included, 9 case series and 1 cohort study, with a total of 192 patients. In all studies, joint denervation improved pain and hand function at follow-up (M = 36.8 months, range = 3-90 months). Pooled analysis of 3 studies on the first carpometacarpal joint showed a statistically significant ( P < .001) reduction in pain scores from baseline (M = 6.61 ± 2.03) to postoperatively (M = 1.69 ± 1.27). The combined complication rate was 18.8% (n = 36 of 192), with neuropathic pain or unintended sensory loss (8.8%, n = 17 of 192) being the most common. This review suggests that denervation may be an effective and low-morbidity procedure for treating arthritis of the hand. Prospective, comparative studies are required to further understand the outcomes of denervation compared with traditional surgical interventions.